The Mediating Role of Preschoolers’ Reading Attitude on the Relationship Between Physical Literacy Environment and English Phonological Awareness among Private Preschoolers in Johor - Yeo, Chie Ling; Chew, Fong Peng; Hutagalung, Fonny Dameaty (Southeast Asia Early Childhood Journal, 2024)
This study examined 374 Malaysian parent-child dyads to explore the mediating role of preschoolers’ reading attitude on the relationship between physical literacy environment and English phonological awareness. Parents provided demographic information and completed a Physical Literacy Environment and Literacy Activities Questionnaire, while children were administered a Phonological Awareness Test and Elementary Reading Attitude Survey. The data were analysed with descriptive statistics and Structural Equation Modelling. Result from the study revealed that there is no relationship between physical literacy environment and reading attitude. Additionally, reading attitude is not the mediator between physical literacy environment and English phonological awareness. These findings suggest that while the physical literacy environment alone may not strongly influence phonological awareness, its impact can be enhanced when combined with factors like parental involvement and effective utilization of resources at home. Parents should be mindful of maintaining an enriching physical literacy environment, including accessible reading materials, appropriate reading spaces, and organized storage for literacy resources.